Effect of corn DDGS on broilers performance and meat quality - Marian Foltyn; Vojtěch Rada; Martina Lichovníková; Eliška Dračková (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2013)
The effects of graded levels of corn distillers dried grains with soluble (DDGS) as partial replacement for soybean meal in diets for broilers were observed. In the first experiment 900 males of ROSS 308 were used and they fed diets with 0, 60, 120 and 180 g/kg DDGS in grower diets (Control group, D6, D12 and D18) from 9th to 35th day of age. In the second experiment 800 broilers both sex of COBB 500 were used and they fed diets with 0 and 200 g/kg DDGS in grower diets (Control group and D20) from 9th to 35th day of age. Until age 30th day there were not significant differences among the groups in live weight in the first experiment. But at 35th day of age the live weight of chickens fed 60 and 120 g/ kg DDGS (2498.5 g and 2496.3 g) was significantly higher (P th to 35th day of age significantly higher (P th day of age was 75.7 g. Feed conversion ratio was similar in all groups in both experiments. There was not observed significant effect of DDGS on weight and proportion of abdominal fat. Feeding DDGS had significant effect (P < 0.05) on decrease the lightness (L*) of breast meat in the first experiment, which was not confirmed in the second experiment.